Sialic Acid-Engineered IL4–10 Fusion Protein is Bioactive and Rapidly Cleared from the Circulation - Cristine Steen-Louws; Peter Boross; Judith Prado; Jan Meeldijk; Jurgen B. Langenhorst; Alwin D. R. Huitema; Marcel T. den Hartog; Louis Boon; Floris P. J. G. Lafeber; C. Erik Hack; Niels Eijkelkamp; Jelena Popov-Celeketic (Pharmaceutical Research, 2020)
Purpose Modulating sialylation of therapeutic glycoproteins may be used to influence their clearance and systemic exposure. We studied the effect of low and high sialylated IL4–10 fusion protein (IL4–10 FP) on in vitro and in vivo bioactivity and evaluated the effect of differential sialylation on pharmacokinetic parameters. Methods CHO cell lines producing low (IL4–10 FP lowSA) and high sialylated (IL4–10 FP highSA) fusion protein were generated. Bioactivity of the proteins was evaluated in an LPS-stimulated whole blood assay. Pharmacokinetics were studied in rats, analyzing plasma levels of IL4–10 FP upon intravenous injection. In vivo activity was assessed in an inflammatory pain mice model upon intrathecal injection. Results IL4–10 FP lowSA and IL4–10 FP highSA had similar potency in vitro . The pharmacokinetics study showed a 4-fold higher initial systemic clearance of IL4–10 FP lowSA, whereas the calculated half-life of both IL4–10 FP lowSA and IL4–10 FP highSA was 20.7 min. Finally, both IL4–10 FP glycoforms inhibited persistent inflammatory pain in mice to the same extent. Conclusions Differential sialylation of IL4–10 fusion protein does not affect the in vitro and in vivo activity, but clearly results in a difference in systemic exposure. The rapid systemic clearance of low sialylated IL4–10 FP could be a favorable characteristic to minimize systemic exposure after administration in a local compartment.

High protein diet induces pericentral glutamate dehydrogenase and ornithine aminotransferase to provide sufficient glutamate for pericentral detoxification of ammonia in rat liver lobules - Louis Boon; Willie J. C. Geerts; A. Jonker; Wouter H. Lamers; Cornelis J. F. Van Noorden (Histochemistry and Cell Biology, 1999)